An Oral Small Molecule VEGFR2 Inhibitor, Apatinib, in Patients with Recurrent or Refractory Cervical Cancer: A Real World Study. (22nd June 2020) - Li, Ning; Wang, Ziyi; Yuan, Guangwen; Sun, Yangchun; Zhang, Rong; Li, Xiaoguang; Li, Nan; Wang, Jing; Wu, Lingying
Abstract : To evaluate the efficacy and safety of apatinib, an oral antiangiogenic drug, in patients with recurrent or refractory cervical cancer as salvage treatment, we retrospectively analyzed the medical records of recurrent or refractory cervical cancer patients admitted to the National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Hunan Cancer Hospital, from October 1, 2016, to December 31, 2017. Patients who progressed within 6 months after the last treatment were given apatinib orally at a dose of 250 mg daily until disease progression or unacceptable toxicity. Twenty-nine patients were enrolled in our retrospective study. Up to February 1, 2019, the median follow-up time was 18 months. The median progression-free survival was 128 days (95% confidence interval (CI): 20–540 days), and the median overall survival was 9 months (95% CI: 4–23 months). The longest period of apatinib administration was 540 days. No complete response was observed, 5 (17.2%) patients achieved partial response, and 11 (37.9%) achieved stable disease. The objective response rate and disease control rate were 17.2% and 55.1%, respectively. The most common adverse events were hypertension (G1, 65.5%, 19/29), mucositis (G1, 55.2%, 16/29), hand-foot syndrome (G1-2, 44.8%, 13/29), and proteinuria (G1-2, 20.7%, 6/29). Grade 3 proteinuria occurred in only one patient (3.4%, 1/29). Apatinib single-agent use might be an effective and tolerable choice as salvage therapy for patients with recurrent or refractory cervical cancer.